Cross-national Analysis of Education and Trust: Context, Comparability, and Causal Mechanisms. Issue 3 (2nd October 2021) - Niedlich, Sebastian
Abstract: Based on existing studies on welfare and education regimes, the paper aims at strengthening the conceptual foundations of comparative research in education and trust by identifying relevant system-level characteristics, deriving analytical dimensions as a framework for cross-national comparison, and exploring how these dimensions might be linked to trust. The paper thus provides a better basis for dealing with context as well as its role in causal explanations and case selection in cross-national comparative research on trust in education.